Improvement of technology of biological purification of waste from sheep farms - Baimukhanbetov, Almas; Bakhtiyar, Balzhan; Tokmoldayev, Amanzhol; Kassym, Ruslan; Tursunbayeva, Gulzhamal; Korobkov, Maxim; Sharipov, Turarbek; Manapova, Gulzagira; Mergalimova, Almagul; Saparov, Dias (Eastern-European Journal of Enterprise Technologies, 2025)
The research focuses on developing and improving biological treatment technologies for agricultural waste to address environmental challenges and enhance sustainability. The object of the study includes various types of agricultural waste, such as crop residues, livestock manure, and processing by-products, which often contribute to pollution and inefficient resource utilization when poorly managed. The primary problem addressed is the need for effective and eco-friendly solutions to mitigate the environmental impact of agricultural waste while maximizing its potential as a resource. Advanced algorithms for optimizing the efficiency and forecasting of energy production have been developed, which have made it possible to achieve a prediction accuracy of 85 %. The combined system has demonstrated a 30 % increase in energy stability compared to using a single renewable source. Adaptive control mechanisms and efficient energy storage management have reduced energy losses in adverse weather conditions by 20 %. These results confirmed the hybrid system’s ability to provide stable electricity, reduce dependence on fossil fuels by up to 40 %, and reduce CO₂ emissions by about 25 %. The study explained these results by demonstrating the synergistic effects of microbial consortia and tailored treatment conditions on waste breakdown and nutrient transformation. Key features of the results include their scalability, cost-effectiveness, and adaptability to different types of agricultural waste. These characteristics allowed the technology to address the problem of inefficient waste management comprehensively